Development of a wearable force-feedback mechanism for free-range haptic immersive experience - Kudry, Peter; Cohen, Michael (Frontiers in Virtual Reality, 2022)
The recent rise in popularity of head-mounted displays (HMDs) for immersion into virtual reality has resulted in demand for new ways to interact with virtual objects. Most solutions utilize generic controllers for interaction within virtual environments and provide limited haptic feedback. We describe the construction and implementation of an ambulatory (allowing walking) haptic feedback stylus with primary use in computer-aided design. Our stylus is a modified 3D Systems Touch force-feedback arm mounted on a wearable platform carried in front of a user. The wearable harness also holds a full-sized laptop which drives Meta Quest 2 HMD, also worn by the user. Such design provides six degrees-of-freedom without tethered limitations, while ensuring high precision of force feedback from virtual interaction. Our solution also provides an experience wherein a mobile user can explore different haptic feedback simulations as well as create, arrange, and deform general shapes.